Islam Dalam Perspektif Al-Qur’an - azzarqa, azzarqa; Mujiburrohman, Mujiburrohman (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2013)
Islam is a immeasurable which has assess and target of very fundamtally, because Islam has side of the truth of absolute which term from al-Qur'an. Word Islam is Shown a name of which is mercy by Allah as a Religion which a later time had made a night of it by Allah to Prophet of Muhammad SAW by the instrumentality of the Angel of Jibril. Bearing Islamic Religion with al-Qur'an very hand in glove once and cannot be disjointed one with is other. Its section of al-Qur'an represent the source of from Islam itself teaching. A lot of sentence of al-qur'an mentioning the name of Islam itself like in Surah al-Baqarah:112, and then Surah Ali Imron:19 and others. In Ianguage context, Islam word in al-Qur'an divided to become two kinds of which among others is islam as sign delivery of self to the infinite, and then secondly islam is as name of from an religion which is marcy by Allah brought by Prophet of Muhammad SAW. Thereby, in comprehending Islam in al-Qur'an, at least relate at two sides, first as a Religion which is genuine as of apocalipse text of ilahiyah and secondly is Islam as a meaning of delivery of it’s self totally to Allah. Among reeling of Islam as a Religion or as form delivery of its self to Allah by all of utilize to reach safety in the world and in eternity.